In Silico Analysis of Functional SNPs in Human CRB2 GENE Associated with Focal Segmental Glomerulosclerosis - Sattar, Imran; Maqbool, Hajira; Aslam, Muhammad Shahbaz; Gull, Iram; Tipu, Imran; Zainab, Mishel (Current Trends in OMICS, 2022)
The CRB2 gene contributes to the onset hereditary focal segmental glomerulosclerosis, which damages the kidney, particularly the glomerulus, and results in chronic kidney failure. The pathogenicity of CRB2 non-synonymous single nucleotide polymorphisms (nsSNPs) was predicted in this work using a variety of bioinformatics techniques for mutation analysis. For this purpose, 1201 nsSNPs from dbSNP-NCBI were retrieved for the analysis, and 20 were predicted deleterious. The 20 missense variants are G349D, C629S, R534W, G178D, C620Y, C620S, R628C, R633G, R633W, E643A, T841M, R960S, R960C, P1064T, P1064S, N800K, G1088D, T1187P, R1249Q, and R1249P. SIFT, PROVEAN, Mutation Assessor, and PANTHER, four sequence homology-based approaches, suggested that one variation, R960S, was benign and that 19 SNPs were deleterious. Six supervised-based approaches, including SNAP2, MutPred2, SuSPect, PhD-SNP, SNPs&Go, and PMut, predicted 14 SNPs as detrimental in all six applied methods. Hence, 13 variations were identified harmful by one structure-based technique, Poly-Phen, and two consensus-based methods, Meta-SNP and Predict-SNP. The CRB2 protein's mutant and wild-type structures were predicted using a laser. Following PyMol 5 structural analysis, the mutations rs879255250 cysteine at 620 changes to tyrosine, variation rs879255250 glycine at 178 changes to aspartate, and variant rs1322315181 glycine at 178 changes to sspartate arginine changes to proline at position 1249, and cysteine changes to serine at position 620, with variants rs147412276 and rs868484209. Proline at position 1064 alterations to serine were expected to be extremely harmful and resulted in structural changes in the protein, which may be candidates for the FSGS etiology. These CBR2 nsSNPs may, thus, be the possibilities for diagnostic genetic screening and therapeutic molecular targeting.